2001
DOI: 10.1063/1.1416141
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of electron irradiated thin polycrystalline CdSe layers

Abstract: Electrical properties of nonirradiated and electron-irradiated thin layers of CdSe, sandwiched between two gold electrodes, were investigated. Thin films of CdSe, prepared by thermal-vacuum evaporation on glass substrate at a temperature of 220 °C, were subjected to two sessions of irradiation with 7 MeV electrons to the fluences of 2×1015 and 4×1015 e/cm2, respectively. The current–voltage characteristics, recorded at temperatures in the range 150–350 K, showed that the Ohm’s law is followed at low-applied vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…7,8 As expected, no detectable structural changes were observed after irradiation. 7,8 As expected, no detectable structural changes were observed after irradiation.…”
Section: Methodssupporting
confidence: 78%
“…7,8 As expected, no detectable structural changes were observed after irradiation. 7,8 As expected, no detectable structural changes were observed after irradiation.…”
Section: Methodssupporting
confidence: 78%
“…As an important II–VI semiconductor material, CdSe has attracted considerable attention due to its unique properties such as a direct bandgap of 1.7 eV and excellent photoelectrical characteristics that makes it a promising material for applications in photoelectronics and photovoltaics 91, 92. Lee and co‐workers fabricated photodetectors with individual single‐crystal CdSe nanoribbons, and studied systematically the photoresponse properties 128, 129, 82.…”
Section: Photodetecting Properties Of 1d Inorganic Nanostructuresmentioning
confidence: 99%
“…Therefore, it has attracted great research attention and has been considered promising in many fields 24 especially for solar energy conversion and optoelectronic applications. 25 Recently, Penner et al ( 26 ) reported a photodetector based on nanocrystalline CdSe nanowires arrays showing fast response times at a range of 20–40 μs but with relatively low gain (0.032–0.050). For single-crystalline CdSe nanowires, Wang et al ( 27 ) reported a photodetector showing rise and decay time constants of 34 and 230 μs, respectively.…”
mentioning
confidence: 99%